Utilization of rapid antigen tests for screening SARS-CoV-2 prior to dental treatment - Pisha Pittayapat; Vorapat Trachoo; Chongpean Jirachoksopon; Kalaya Udom; Chunya Champakerdsap; Oraphan Rungrojwittayakul; Paksinee Kamolratanakul; Pairoj Linsuwanont; Lawan Boonprakong; Natthavoot Koottathape; Vitara Pungpapong; Thanaphum Osathanon; et al. (Frontiers Media S.A., 2022)
Potential aerosols containing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral particles can be generated during dental treatment. Hence, patient triage is essential to prevent the spread of SARS-CoV-2 in dental clinical settings. The present study described the use of rapid antigen tests for SARS-CoV-2 screening prior to dental treatment in an academic dental clinical setting in Thailand during the pandemic. The opinions of dental personnel toward the use of rapid antigen test screening prior to dental treatment were also assessed. From August 25 to October 3, 2021, dental patients who were expected to receive aerosols generating dental procedures were requested to screen for SARS-CoV-2 using a rapid antigen test before their treatment. A total of 7,618 cases completed the screening process. The average was 212 cases per day. Only five patients (0.07%) were positive for SARS-CoV-2 in the rapid antigen screening tests. All positive cases exhibited mild symptoms. For the questionnaire study, experienced dental personnel frequently and consistently agreed with the use of the rapid antigen test for SARS-CoV-2 screening, which made them feel safer during their patient treatment. However, implementing rapid antigen tests for SARS-CoV-2 may increase the total time spent on a dental appointment. In conclusion, a rapid antigen test could detect the infected individual prior to dental treatment. However, the specificity of rapid antigen tests for SARS-CoV-2 must be taken into account for consideration as a screening process before dental treatment. The enhanced infection control protocols in dental treatment must be consistently implemented.